Bioeconomic evaluation of extended season and year-round tomato production in Norway using supplemental light. (April 2022) - Naseer, Muhammad; Persson, Tomas; Righini, Isabela; Stanghellini, Cecilia; Maessen, Henk; Ruoff, Peter; Verheul, Michel J.
Abstract: CONTEXT: For high latitude countries like Norway, one of the biggest challenges associated with greenhouse production is the limited availability of natural light and heat, particularly in winters. This can be addressed by changes in greenhouse design elements including energy saving equipment and supplemental lighting, which, however, also can have a huge impact on investments, economic performance, resources used and environmental consequences of the production. OBJECTIVE: The study aimed at identifying a greenhouse design from a number of feasible designs that generated highest Net Financial Return (NFR) and lowest fossil fuel use for extended seasonal (20th January to 20th November) and year-round tomato production in Norway using different capacities of supplemental light sources as High Pressure Sodium (HPS) and Light Emitting Diodes (LED), heating from fossil fuel and electricity sources and thermal screens by implementing a recently developed model for greenhouse climate, tomato growth and economic performance. METHODS: The model was first validated against indoor climate and tomato yield data from two commercial greenhouses and then applied to predict the NFR and fossil fuel use for four locations: Kise in eastern Norway, Mære in mid Norway, Orre in southwestern Norway and Tromsø in northern Norway. The CO2 emissions for natural gas used for heating the greenhouse and electricity used for lighting were calculated per year, unit fruit yield and per unit of cultivated area. A local sensitivity analysis (LSA) and a global sensitivity analysis (GSA) were performed by simultaneously varying the energy and tomato prices. RESULTS AND CONCLUSIONS: Across designs and locations, the highest NFR for both production cycles was observed in Orre (116.9 NOK m −2 for extended season and 268.5 NOK m −2 for year-round production). Fossil fuel was reduced significantly when greenhouse design included a heat pump and when extended season production was replaced by a year-round production. SIGNIFICANCE: The results show that the model is useful in designing greenhouses for improved economic performance and reduced CO2 emissions from fossil fuel use under different climate conditions in high latitude countries. The study aims at contributing to research on greenhouse vegetable production by studying the effects of various designs elements and artificial lighting and is useful for local tomato growers who either plan to build new greenhouses or adapt existing ones and in policy formulation regarding incentivizing certain greenhouse technologies with an environmental consideration or with a focus on increasing local tomato production. Graphical abstract: Unlabelled Image Highlights: A simulation model was applied to evaluate greenhouse design elements with artificial light in Norway; The economic and environmental performance of extended season and year round tomato production was determined; Observed temperature, CO2 -concentration and yield were predicted fairly accurately; For year-round, the design with day and night thermal screens, heat pump and top and inter-lighting LED had the highest NFR; High-tech energy saving equipment has better results for greenhouse tomato production in colder regions than standard designs.